ACUPUNCTURE IMPROVES THE EFFECTS OF CHINESE HERBAL MEDICINE IN TREATING ENDOMETRIOSIS MODEL RATS - J. Shi; Z. B. Z. Ge; Y. Jin; Y. D. Li; J. Zhou (Journal of Animal and Plant Sciences, 2013)
The present study was aimed to investigate whether acupuncture could significantly enhance the efficacy of Chinese herbal medicine (CHM) in treating endometriosis model rats. A total of 40 female Sprague-Dawley (SD) rats with body weight of 200 ±20 g were included. Operational transplantation was used with animal models. The rats were randomly divided into 5 groups: sham-operation control group (Group A), model group (Group B), CHM combined with acupuncture group (Group C), CHM group (Group D), Danazol group (Group E) with 8 rats in each group. During the treatment, two rats in Group B and one rat in Group E passed away. When the treatment ended, all the left rats were sacrificed. The samples of peritoneal fluids, serum and the ectopic endometrium were taken. The serum levels of cancer antigen 125 (CA-125) and interleukin 18(IL-18) in the peritoneal fluids were detected using enzyme-linked immune-sorbent assay. The cyclooxygenase-2 (COX-2) mRNA expression levels in the ectopic endometrium were measured by Real-time PCR. The results showed that in the rats from Groups A, C, D and E, the serum CA-125 levels, COX-2 mRNA expression in the ectopic endometrium and the IL-18 levels in the peritoneal fluids were significantly lower than those of Group B (P0.05). The levels of IL-18 in the peritoneal fluids of the rats in Group C were markedly lower than those of Group D and E (P<0.05). It is then concluded that acupuncture treatment can improve the effects of CHM in treating endometriosis model rats.
Keywords: Chinese herbal medicine acupuncture; endometriosis